Digitized Teaching Strategy (DigiTS) in Improving the Language Performance on Basic Figures of Speech - Marvin John C. Corpuz (Future Science, 2024)
Digitized learning materials offer students meaningful classroom learning experiences that may actively engage the students in the learning process toward holistic development. Hence, this action research aimed to determine the effectiveness of the Digitized Teaching Strategy (DigiTS) in improving the English language performance of Grade 8 students in Gen. Tiburcio de Leon National High School using researcher-made tests and group discussions. Participants were 60 Grade 8 students divided into two groups-the control group who received the traditional method of teaching and the experimental group who were exposed to the Digitized Teaching Strategy. The study employed a mixed method research design which included pre-test, post-test, and Focus Group Discussion. Data were analyzed quantitatively using appropriate statistical treatment and qualitatively through coding and categorizing. Findings of quantitative data analysis revealed that both the traditional way of teaching and Digitized Teaching Strategy (DigiTS) improved the English language performance of the students as shown by the mean scores during pre-test and post-test. However, the performance of the experimental group had no significant difference to the performance of the control group based on the statistical computation. On the other hand, qualitative data analysis had identified three recurring themes- development of basic language skills, motivation for positive learning engagement, and teachers’ involvement in learning. Though participants agreed that DigiTS was an engaging way of teaching and learning that could develop their English macro skills, students believed that teachers’ in-depth discussion is necessary to ensure mastery of the lesson. The study recommends that teachers in different disciplines must familiarize the process of crafting potential materials to cater 21st century learners’ needs. The Digitized Teaching Strategy (DigiTS) can also be used to aid teachers on lesson delivery to ease their teaching tasks without compromising the quality.